THE EFFECT OF ALLOGENIC FREEZE DRIED PLATELET-RICH PLASMA IN RESPONSES INFLAMMATION REACTION OF RABBIT - rachmawati, trio (Stem Cell Research and Development Center, Universitas Airlangga, 2017)
This study aims to analyze the effects of allogenic freeze dried platelet-rich plasma in responses inflammation reaction of rabbit. The designs of this study are one group pretest posttest conducted to determine the effect of freeze drying on levels of TGF-β1 PRP and post test only control group design conducted to determine the effect of allogenic freeze dried PRP. Nine samples of PRP which examined levels of TGF-β1 before and after freeze drying were obtained from blood centrifugation of three rabbits. These nine samples were used as allogenic donor which injected intramuscularly in nine rabbits for the treatment groups. The control group used nine rabbits which was injected intramuscularly using autologous PRP. Both groups were observed inflammatory response. Measurement of TGF-β1 levels before and after freeze drying were tested statistically using T- test dependent. Data inflammatory response were tested statistically using T- test independent. The results showed that no effect of freeze drying process on levels of TGF-β1. Allogenic freeze dried PRP did not cause an iflammatory response.Keywords : autologous, allogenic, freeze dried platelet rich plasma, transforming growth factor- β1.